State of post-pandemic development of the housing market of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2022)
The development of the housing market of the Republic of Kazakhstan in 2020 was predeterminedby important factors – the unfavorable economic situation caused by COVID-19 and the spread of thisvirus. The main purpose of this article is to analyze and assess the dynamic development of the housingmarket of the Republic of Kazakhstan in the context of COVID-19 when compared with the crisis yearof 2014 and analyze the potential consequences. Thanks to the collection and analysis of statistical dataand continuous monitoring of the housing market, conclusions were drawn about serious changes, bothin market directions and in systemic changes in the state housing policy. In the article, using methodsof comparative analysis, trends in the development of the housing market are identified, key factors influencingthe annual dynamics of real estate prices are identified; their quantitative impact was assessedusing correlation analysis and econometric models of the impact of these factors on the average housingprice by the population were evaluated and the permissible consequences of restrictions and measuresintroduced in connection with the pandemic were determined. Recommendations are proposed to supportthe housing market of the Republic of Kazakhstan, stimulating the development and coverage of allmarket entities. The results obtained will be useful to researchers, organizers of investment projects andrepresentatives of government bodies.Key words: Housing market, COVID-19, housing prices, government regulation, mortgages.